2021
DOI: 10.7150/jca.61249
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serological markers of hepatitis B virus infection in squamous cell cervical cancer

Abstract: Objective: The current study aimed to investigate the prognostic value of serological markers of hepatitis B virus (HBV) infection in squamous cell cervical cancer. Methods: Squamous cell cervical cancer patients treated by concurrent chemoradiotherapy from January 2013 to December 2015 at Yunnan Cancer Hospital were retrospectively reviewed. Results: Of a total of 277 patients, 12 (4.33%), 93 (33.57%), 2 (0.72%), 25 (9.02%), and 36 patients (13.00%) were seropositive for hepatitis B surface antigen (HBsAg), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The association between HPV infection and cervical cancer development has been established, where the evidence demonstrated a high concurrent rate of HBV and HPV co-infection (118, 119). Subsequently, recent hospital-based and epidemiological studies investigated the influence of HBV infection on cervical cancer development and prognosis (8,12,(120)(121)(122). However, the influence of HBV infection on cervical cancer risk is debated.…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The association between HPV infection and cervical cancer development has been established, where the evidence demonstrated a high concurrent rate of HBV and HPV co-infection (118, 119). Subsequently, recent hospital-based and epidemiological studies investigated the influence of HBV infection on cervical cancer development and prognosis (8,12,(120)(121)(122). However, the influence of HBV infection on cervical cancer risk is debated.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Therefore, the conclusion for the causal effect between HBV infection and cervical cancer risk requires further evaluation with more comprehensive clinical information. An increasing number of studies revealed that anti-HBs seropositivity and prior HBV infection might be independent favorable prognostic factors for the OS and DFS of patients with cervical cancer (120,121), whereas HBx protein exerted an adverse effect on cervical cancer progression (122). Accordingly, in-depth explorations of the interaction between HBV and HPV in inducing the carcinogenesis of cervical lesions and the immune microenvironment in HPV infection patients with cervical cancer with prior HBV infection could aid understanding of the role of HBV infection status and anti-HBV treatment in cervical cancer risk and future prognosis.…”
Section: Cervical Cancermentioning
confidence: 99%
“… 12 In contrast, HBV infection is reportedly an independent favorable prognostic factor in patients with esophageal cancer who underwent esophagectomy, 13 with no survival influence in patients with squamous cell cervical cancer. 14 …”
Section: Introductionmentioning
confidence: 99%
“…HBV infection correlates with a poor prognostic outcome in patients with pancreatic cancer, 8 nasopharyngeal carcinoma (NPC), 9 advanced non‐small cell lung cancer (NSCLC), 10 breast cancer, 11 and ovarian cancer 12 . In contrast, HBV infection is reportedly an independent favorable prognostic factor in patients with esophageal cancer who underwent esophagectomy, 13 with no survival influence in patients with squamous cell cervical cancer 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation